Intestinal Malrotation, Mesocolic Hernia, and Meckel Diverticulum – Differential Diagnosis of Abdominal Pain in Adults: Case Report and Literature Review - Costa, Marcus Vinícius Silva; Alencastro, Márcia Cristina de; Linica, Samyra Braz de; Ferreira, Tiago dos Santos; Bezerra, Edson Soares; Bisogni, Sérgio (Journal of Coloproctology, 2021)
Intestinal malrotation is a congenital anomaly caused by incomplete rotation or absence of rotation of the primitive intestine along the axis of the upper mesenteric artery during embryonic development. Embryonic development and its anatomical variations were described by Dott in 1923.Intestinal malrotation is a rare condition among adults – prevalent in a mere 0.0001% to 0.19% of the population –, and it may be associated with other anatomical deformities. It can be asymptomatic or manifest with varying intensity, from obstruction to necrosis of intestinal segments. In general, this abnormality is diagnosed in the first year of life; however, symptoms may appear later in life, making diagnosis in adults difficult on account of non-specific symptoms.In the present study, we report a case of intestinal malrotation associated with chronic non-specific symptoms progressing to mesenteric angina.
Keywords: intestinal malrotation; Meckel diverticulum; intestinal angina; Ladd procedure; chronic abdominal pain